2021
DOI: 10.29219/fnr.v65.5501
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining household-level food insecurity during COVID-19 epidemic: a case of Wuhan, China

Abstract: Background: In coping with the coronavirus disease 2019 (COVID-19) epidemic, cities adopted social isolation and lockdown measures; however, little is known about the impacts of these restrictions on household food security. Objective: This study provides a timely assessment of household food insecurity (HFI) in the Chinese city of Wuhan during the COVID-19 epidemic period and also investigates its determinant factors. Design: We collected valid data on food insecurity from 653 households in Wuhan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Research in Bangladesh showed that food insecure households during pandemic were 88.68% 36 . A study in Wuhan, China showed that 94% of households were food insecure in March 2020 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Research in Bangladesh showed that food insecure households during pandemic were 88.68% 36 . A study in Wuhan, China showed that 94% of households were food insecure in March 2020 37 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Wuhan had a population of over 9 million registered residents (Zhang et al. 2021) and another 4–5 million “nonresidents who frequently move in and out for business, work, and tourist purposes” (Bian et al. 2020, 420).…”
Section: Wuhan Food Provisioning Under Blockaded Lockdownmentioning
confidence: 99%
“…During the 2019–2020 winter holidays, millions of registered inhabitants left Wuhan for vacations (Zhang et al. 2021); millions of nonresidents came to visit family members (Qian and Fan 2020; Zhu and Cai 2020); and unknown numbers of nonresident migrants arrived or departed for seasonal festival work (Zhao, Liu, and Zhang 2018). The estimated 11 million still in Wuhan on January 23, 2020—whether lifelong residents, winter holiday visitors, or temporary migrant workers—went without warning abruptly under government‐blockaded lockdown.…”
Section: Wuhan Food Provisioning Under Blockaded Lockdownmentioning
confidence: 99%
See 2 more Smart Citations